Current and future approaches to large airways imaging in adults and children. Issue 5 (May 2017) - Semple, T.; Calder, A.; Owens, C.M.; Padley, S.
Abstract : "Large airways disease" is a catch-all phrase encompassing a wide variety of pathology affecting the trachea, main, lobar, segmental, and proximal sub-segmental bronchi. Relevant pathologies can be divided into focal or diffuse processes and many conditions have classic appearances on computed tomography (CT). We provide a review of the imaging specifics of a wide range of large airway pathologies in adult, childhood, and fetal life with examples of common and rare pathologies ranging from well-known entities such as cystic fibrosis and allergic bronchopulmonary aspergillosis to rarities such as Williams–Campbell, primary ciliary dyskinesia, and congenital high-airway obstruction syndrome (CHAOS). Although the spatial and temporal resolution of modern multidetector CT lends itself well to the depiction of small structures such as the peripheral airways, concerns regarding radiation exposure and increasing interest in the role of functional and quantitative imaging have led to a surge in research into dose reduction in CT and both structural and functional airway imaging via magnetic resonance imaging. We discuss the current literature on these emerging techniques along with some exiting near future directions for large airways imaging.